Analisis Koefisien Aliran Menggunakan Metode Cook di DAS Klagison Kota Sorong - Marzuki, Irwanto; Farida, Anif; Rusdi, Achmad (Dinamika Lingkungan Indonesia, 2024)
The Klagison River Watershed has an area of 1.997,6 ha and is experiencing rapid development in the physical field. The problem that often occurs in the Klagison watershed is that when there is heavy rain, several places close to the river will experience flooding, which is caused by several factors, one of which is the runoff coefficient. The aim of this study was to analyze the runoff coefficient of Klagison watershed. The method used to analyze the runoff coefficient is Cook's method, through the analysis of Geographic Information Systems (GIS) on several maps, such as maps of slope, vegetation cover, flow density, and soil infiltration. The results showed that the distribution of runoff coefficients that occurred in the Klagison watershed was dominated by the high class of 69,919% with an area of 13,967 km², the normal class of 21,500% with an area of 13,967 km², and the extreme class of 8,580% with an area of 1,714 km². Overall, the Klagison watershed is included in the high category with a runoff coefficient value of 62,603 %. This means that from 100% of the rain that falls, 62,603% will flow and 37,397% will infiltrate into the ground.